Emergency Room Nurses‟ Views on Bedside Shift Reporting (International Journal of Studies in Nursing, 2019)
Bedside shift reporting is a form of communication used by nurses to communicate with each other regarding the patient plan of care. Although bedside shift reporting is required by The Joint Commission and is a required hospital policy, there are inconsistencies in the emergency room nurses performing the task. The purpose of this study was to describe emergency room nurses‟ views on bedside shift reporting. A qualitative research study was conducted using a semi-structured interview process. Colaizzi‟s data collection and analysis strategy were used to determine emerging themes. Peplau‟s interpersonal relations and Benner‟s novice to expert theories were used to help guide this study. Fifteen emergency room nurses were interviewed, and seven themes emerged from the data collected. Three themes, nurse accountability, nurse introduction, and patient involvement were identified as benefits of bedside shift reporting. Four themes, bedside shift report not done, emergency room situations, emergency room environment, and time factors were identified as challenges of bedside shift reporting. The study helped to determine the need for additional educational opportunities for the emergency room nurses, emergency department, and the organization to increase the consistency of the reporting process.